Laser processing of TiO2 films for dye solar cells: a thermal, sintering, throughput and embodied energy investigation. (17th August 2012) - Mincuzzi, G.; Schulz‐Ruhtenberg, M.; Vesce, L.; Reale, A.; Di Carlo, A.; Gillner, A.; Brown, T. M.
ABSTRACT We have analysed and optimised a laser process for the sintering of the TiO2 layers in dye solar cells (DSCs). Through a thermographic characterisation of the process, we show that it is possible to scale and process large areas uniformly (16 cm2). We fabricated DSCs with nanocrystalline (nc)‐TiO2 films sintered by using pulsed ultraviolet laser with an average output power P varying from 1 W to 7 W whilst mainting a constant power conversion efficiency η. The highest efficiency reached for a laser sintered DSC was 7%. The time required to sinter 1 m2 of nc‐TiO2 film was found to decrease hyperbolically with P, which is important for determining process takt times. We quantified the embodied energy (EE) required to sinter 1 m2 of the active TiO2 layer for a variety of different processes, and found that the EE for the laser sintering process with a system wall plug efficiency of 3.5% to be competitive with the more conventional oven and belt furnace treatments. We outline the main features required from a laser system to carry out an efficient, energetically favourable and industrially applicable automated process with competitive throughput. Copyright © 2012 John Wiley & Sons, Ltd.